2012
DOI: 10.1371/journal.pone.0049877
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a Conserved Sequence Motif in Transmembrane Segment S3 for the Gating of Human TRPM8 and TRPM2

Abstract: For mammalian TRPM8, the amino acid residues asparagine-799 and aspartate-802 are essential for the stimulation of the channel by the synthetic agonist icilin. Both residues belong to the short sequence motif N-x-x-D within the transmembrane segment S3 highly conserved in the entire superfamily of voltage-dependent cation channels, among them TRPM8. Moreover, they are also conserved in the closely related TRPM2 channel, which is essentially voltage-independent. To analyze the differential roles of the motif fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…It is understandable that no selection occurred in the transmembrane segments because any change in these would destroy the transmembrane structure (Winking et al, 2012). Interestingly, no selected site was identified in the intracellular linkers between S2 and S3, and between S4 and S5, further supporting our notion that the external side is important for responding to temperature alterations.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is understandable that no selection occurred in the transmembrane segments because any change in these would destroy the transmembrane structure (Winking et al, 2012). Interestingly, no selected site was identified in the intracellular linkers between S2 and S3, and between S4 and S5, further supporting our notion that the external side is important for responding to temperature alterations.…”
Section: Discussionsupporting
confidence: 68%
“…It has also been suggested that the extracellular Ploop is a critical structure for temperature sensitivity (Winking et al, 2012;Yang et al, 2010). In present study, we investigated the molecular evolution of thermo-TRP channel genes across vertebrate phylogeny and addressed the question of how natural selection has acted on the structure and functions of cold and heat receptors in order to understand how animal preferences for hot versus cold sensitivity have evolved.…”
Section: Introductionmentioning
confidence: 99%
“…The NxxD motif could represent a sensor in mechanosensation since mutant channels shift the activation curves to membrane tensions less than those required to activate the wild-type MscL [43]. As this motif is also a functional component of the V-sensor in voltagedependent channels, mutations of this region are likewise critical in channel gating [27,44,45]. Interestingly, in MscL orthologues, two helical turns below the NxxD motif, a conserved Gly residue (G24 in M. tuberculosis) forms a girdle surrounding the narrowest portion of the channel lumen [46].…”
Section: Resultsmentioning
confidence: 99%
“…In TRP channels, which are weakly voltagesensitive but strongly activated by stimuli as diverse as heat, cold, and several ligands, gating is also achieved through conformational changes facilitated by local flexibility. These motions are associated with specific regions of the VSD, including the S3 segment, as well as linkers S3-S4L and S4-S5L [9,[27][28][29]. In CNG channels, which are virtually voltage-independent, the opening of the pore has evolved in strict dependence on the cyclic nucleotide-binding through conformational changes involving the S4-S5L [30].…”
Section: Introductionmentioning
confidence: 99%
“…TRPM8 also act as a voltage gated ion channel which becomes activated upon membrane depolarization [32][33][34]. Indeed, a small yet highly conserved (in many ion channels) region located in the transmembrane region 3 (TM3) of TRPM8 can act as a "voltage-sensor" [35]. Similarly, a small double cysteine motif is important for TRPM8 channel functions [36].…”
Section: Introductionmentioning
confidence: 99%